2022
DOI: 10.1080/14756366.2022.2080818
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, purification, kinetic and anion inhibition studies of a recombinant β-carbonic anhydrase from the Atlantic salmon parasite platyhelminth Gyrodactylus salaris

Abstract: A β-class carbonic anhydrase (CA, EC 4.2.1.1) was cloned from the genome of the Monogenean platyhelminth Gyrodactylus salaris, a parasite of Atlantic salmon. The new enzyme, GsaCAβ has a significant catalytic activity for the physiological reaction, CO 2 + H 2 O ⇋ HCO 3 − + H + with a k cat of 1.1 × 10 5 s −1 and a k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…CAs are associated with the performance of various integral physiological functions within living organisms. Firstly, organisms belonging to the taxonomic class of vertebrates are mostly categorized into the α-CA gene family which consists of various molecular conformations of the target enzyme [4,6,[10][11][12][13][14][15][16][17][18][19]. The main biological function of CA includes the reversible hydration of carbon dioxide to bicarbonate and hydrogen ions for maintaining the proper pH homeostasis and their involvement in biosynthetic reactions like gluconeogenesis and ureagenesis in mammals [4].…”
Section: Introductionmentioning
confidence: 99%
“…CAs are associated with the performance of various integral physiological functions within living organisms. Firstly, organisms belonging to the taxonomic class of vertebrates are mostly categorized into the α-CA gene family which consists of various molecular conformations of the target enzyme [4,6,[10][11][12][13][14][15][16][17][18][19]. The main biological function of CA includes the reversible hydration of carbon dioxide to bicarbonate and hydrogen ions for maintaining the proper pH homeostasis and their involvement in biosynthetic reactions like gluconeogenesis and ureagenesis in mammals [4].…”
Section: Introductionmentioning
confidence: 99%
“…These proteins, which facilitate the conversion of carbon dioxide to bicarbonate while releasing a proton, play a vital role in various physiological processes related to respiration and the transportation of CO 2 /bicarbonate between metabolizing tissues and lungs [7,8]. They are also involved in maintaining pH and CO 2 balance, regulating electrolyte secretion in different tissues and organs, facilitating biosynthetic reactions (such as gluconeogenesis, lipogenesis, and ureagenesis) [919], promoting bone resorption, and influencing tumorigenicity as well as other physiological and pathological processes [7,8,14,19]. Mtb possesses three β-CA genes in its genome: Rv1284 (which encodes a protein referred to as Mtb β-CA1), Rv3588c (which encodes Mtb β-CA2), and Rv3273 (which encodes a third enzyme known as Mtb β-CA3) [19].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, CAs from pathogens started to be considered as possible targets for the development of antiinfectives, for the management of diseases provoked by bacteria 21 , fungi 22 , protozoa 23 and worms 10 , 11 , 24 . In the previous work 1 we have shown that GsaCAβ has a significant catalytic activity for the physiologic, CO 2 hydration reaction, with a k cat of 1.1 × 10 5 s −1 and a k cat / K m of 7.58 × 10 6 M −1 × s −1 . Furthermore, inorganic anions, a well-known class of CA inhibitors (CAIs) 14 , 15 inhibit the enzyme in the millimolar range, as for other α- and β-CAs investigated for their interaction with such modulators of activity 14 .…”
Section: Introductionmentioning
confidence: 95%
“…We have recently reported the cloning and characterisation of a β-class carbonic anhydrase (CA, EC 4.2.1.1) encoded in the genome of Gyrodactylus salaris , GsaCAβ 1 , a platyhelminth (flatworm) parasite attacking various fish species 2 , 3 . The Atlantic salmon ( Salmo salar ) is particularly sensitive to this parasite, which produced catastrophic losses in fish farms in Scandinavian countries and elsewhere, starting with the 1970s 3–5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation